THE SCOPE AND NATURE OF AYURVEDA - Vyas, Vasudev V. (Medknow Publications & Media Pvt Ltd, 1982)
Ayurveda, which means the Science of life is erroneously understood and propagated by some of the scholars as just one of the traditional systems of medicine. It encompasses the entire gamut of human life aiming on projection of total personality, mental, physical and intellectual. Ayurveda's concept of diseases and treatments are different from other systems of medicine and with its wide scope embracing preventive, curative and positive aspects. Ayurveda belongs to a class by itself, unique and distinct